Pelatihan Konten Kreator Media Pembelajaran Online Di SMK Yasiha Gubug - Kurniawati Kurniawati; Lenny Kurniati; Adi Nova Trisetyanto; Banun Sri Haksasi (Lembaga Pengembangan Kinerja Dosen, 2023)
The Covid-19 pandemic has brought significant changes in various aspects of life, including the education sector. One of the noticeable changes is the shift to online learning. However, the problem faced by teachers in this online learning process is the lack of skills in selecting relevant learning media that suits the condition and needs of the students. Therefore, the aim of this community service program is to provide an understanding of the concept of online learning media and to introduce and improve the teachers' ability in using the online learning support system through training and mentoring in creating online learning media content, particularly through the YouTube platform, for teachers at SMK Yasiha Gubug. The method used in this community service program was an informative approach and training mentoring. The results of this program showed that the motivation, confidence, understanding of online learning media, and teachers' skills in using technology to create online learning media have improved.